Analysis of germplasm resources by simple sequence repeat markers in Cymbidium hybridum - SHEN Hongzhe; LI Chunnan; FU Qiaojuan; CUI Hairui (浙江大学学报. 农业与生命科学版, 2022)
Sixty-eight simple sequence repeat (SSR) primer pairs were designed based on the transcriptome data of Cymbidium faberi and 25 primer pairs with stable amplification and better polymorphism were selected for genetic diversity analysis of 41 C. hybridum cultivars. The results showed that a total of 187 SSR bands were amplified, and 171 (91.44%) of them were polymorphic with the average of 6.84 bands per primer pair. The mean value of polymorphism information content (PIC) and the number of genotypes per SSR marker were 0.770 3 and 12.88, respectively. Genetic similarity coefficient among 41 cultivars ranged from 0.57 to 0.99 with an average of 0.72. A dendrogram of genetic relationship constructed using unweighted pair-group method with arithmetic mean (UPGMA) showed that the tested accessions could be classified into five clustering groups with the similarity coefficient of 0.71, which were consistent to some extent with the plant size, branch type and flower color. The above results reveal the genetic diversity and relationships among the tested accessions. The newly developed SSR markers will be useful tools for molecular breeding of C.hybridum.